Composting as a strategy to recycle aquatic animal waste: Case study of a research centre in São Paulo State, Brazil - Lopes, Ivã Guidini [UNESP]; de Souza, Luiz Fernando [UNESP]; da Cruz, Mara Cristina Pessôa [UNESP]; Vidotti, Rose Meire [UNESP] (SAGE Publications, 2019)
Aquaculture is a fast-growing activity in Brazil and around the world, which generates large amounts of waste from fingerling production to the final consumer. Among several possibilities for the management of these wastes, windrow composting stands out as a simple and low-cost method. In this study, 16 composting piles were assembled with wood shavings and peanut shells and managed according to two methods; one with carcasses recharges and another without. A description of the daily occurrences and management details were made. Temperature and moisture content were monitored and at the end of the decomposition process, and after 60 and 100 days of curing, physic-chemical analysis was performed to assess composts quality. A germination index test was performed to assess composts phytotoxicity. All piles exceeded 55 °C for more than 15 days (with the aid of turnings) and germination indices were above 50% for both lettuce and cress seeds. Total nitrogen concentration among composts varied from 22.1 to 33.2 g kg-1 and carbon:nitrogen ratios were below 20, while pH values were above 6.0 in all composts. Curing composts for 60 and 100 days did not influence any of the physic-chemical characteristics of all composts, so this practice can be dodged, thus avoiding unnecessary land use and increasing production costs. The type of management adopted for carcasses of aquatic animals influenced total and inorganic nitrogen, C/N ratio, organic matter and pH values of the composts, being recommended the recharge of carcasses to improve composts stability and quality.
Keywords: Aquaculture; compost; curing; ecotechnology; environment; residues